2021
DOI: 10.1039/d1sc04486a
|View full text |Cite
|
Sign up to set email alerts
|

A stable triplet diradical emitter

Abstract: Stable borocyclic diradical emitters with a tunable ground state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 55 publications
(19 reference statements)
0
20
0
Order By: Relevance
“…Two dioxoborocyclic diradicals, B-N15a and B-N15b , were synthesized by reacting B-PN15a ( B-PN15b ) with chlorobis(perfluorophenyl)borane and K in THF (Scheme 26). 49 The two BO 2 C 2 rings of B-N15a and B-N15b are coplanar with pyrenetetraone backbones. The bond parameters of the BO 2 C 2 rings are similar to that in B-N15a and B-N15b , indicating that the unpaired electrons are mainly delocalized over the two BO 2 C 2 rings.…”
Section: Group 13 Element Radicalsmentioning
confidence: 99%
“…Two dioxoborocyclic diradicals, B-N15a and B-N15b , were synthesized by reacting B-PN15a ( B-PN15b ) with chlorobis(perfluorophenyl)borane and K in THF (Scheme 26). 49 The two BO 2 C 2 rings of B-N15a and B-N15b are coplanar with pyrenetetraone backbones. The bond parameters of the BO 2 C 2 rings are similar to that in B-N15a and B-N15b , indicating that the unpaired electrons are mainly delocalized over the two BO 2 C 2 rings.…”
Section: Group 13 Element Radicalsmentioning
confidence: 99%
“…Electron paramagnetic (EPR) spectroscopy of the electrogenerated solution confirmed that paramagnetic species were present, which could correspond to residual Ph4-5-CML − or to the triplet state of Ph4-5-CML 2-(SI Figure S23). 48 This is in contrast to other deeply reducing photocatalysts that degrade to diamagnetic species under catalytic conditions. 14,22 When Ph4-5-CML 2-and a large excess of 26 were mixed together, significant quenching of the absorbance of Ph4-5-CML 2− was observed (Figure 2c).…”
Section: Resultsmentioning
confidence: 95%
“…As the singlet-triplet energy gap affects the population of singlet and triplet species at different temperatures, it also affects the contribution of singlet and triplet excitations to the optical absorption of diradicals. 194,195 Although thermal and optical excitations of diradicals are sometimes mixed and thereby inconsistently reported in the literature, our goal herein is to highlight some of the previously published molecules and thereby motivate more research efforts in the field. Lee et al 196 and Rajca et al 197 have discussed design strategies for high-spin molecules (total spin, S Z 1) from computational and synthetic points of view, respectively.…”
Section: Diradicals and Their Resonance Formsmentioning
confidence: 99%